Playing with Pop-up Books to Reduce Preschool Children's Anxiety - Yunike; Rehana; Luthfiyah Nur Aisyah (Journal of Applied Holistic Nursing Science, 2024)
Background: Acute typhoid fever is an acute infectious systemic disease caused by the microorganism Salmonella enterica serotype Typhi, commonly known as Salmonella typhi. One of the issues that arises is anxiety due to hospitalization. The implementation of distraction techniques can help reduce anxiety caused by hospitalization. Methods: This research design uses a descriptive method in the form of a case study. The approach includes Nursing Care, planning, implementation, evaluation, and nursing documentation. The research subjects consist of two individuals with the same issue, namely typhoid fever patients. This study was conducted at Siti Fatimah Hospital in South Sumatra from April 8 to 13, 2024. Results: The study found that the distraction technique performed over three consecutive days resulted in a decrease in anxiety levels. Conclusion: The research findings highlight the need for distraction technique interventions to address anxiety.